“Fear (not)!” - emotion and ethics in Deuteronomy - Kipfer, Sara; Wright, Jacob L. (Journal of ethics in Antiquity and Christianity, 2020)
Fear is an emotion that is often expressed in a bodily reaction and that frequently leads to a concrete action. It is thus not surprising that the conceptualization of fear in the book of Deuteronomy is strongly linked to the activation and moral formation of both individual and community. On the one hand, and especially in the book’s eve-of-battle rhetoric, fear is something to be avoided and confined so that it does not contaminate the entire community (“fear not!”). On the other hand, when its object is the nation’s deity, fear is something to be learned and taught (“so that they may learn to fear me… and teach their children for ever”). In both capacities, fear in Deuteronomy has an extraordinary potential to shape the social order. It has a key role to play in stabilizing society and promoting both collective and individual flourishing, while also being understood as a destabilizing, destructive force that is to be quarantined as if it were a contagious virus.